Tithorea, Griechenland. Topographische Untersuchungen im Stadtgebiet. Die Arbeiten der Jahre 2016 und 2017 - Sporn, Katja; Laufer, Eric (e-Forschungsberichte des DAI, 2019)
In 2016, new archaeological fieldwork at Phokian Tithorea was started by two Ephorates and supported by the German Archaeological Institute Athens (since 2017 a perpetuated cooperation). The fieldwork of 2016/2017 was focussed on cleaning, measuring, and studying the very well preserved 4th century BC fortification of the city as well as the upper intraurban area which is divided by a diateichisma and terrace walls. Furthermore, in an area of caves towering the area of the ancient city, evidence of human occupation during antiquity has been surveyed. The project will be continued in 2018 and beyond with extended landscape fieldwork in the Phokian Kephissos plain around Tithorea.